Disparities in availability of new cancer drugs worldwide: 1990-2022 - Meng Li; Qiushi Chen; DukHee Ka (BMJ Global Health)
Introduction Despite progress in the development of new cancer drugs, concerns about equity of access remain. This study aimed to examine the availability and timeliness of availability of new cancer drugs around the globe over the past three decades and their associations with country characteristics.Methods From a pharmaceutical intelligence database we identified new cancer drugs launched between 1990 and 2022. We calculated the number of new drugs launched in each country and the delay in launches. Using a multivariable linear regression and a Cox regression model with shared frailty, we examined the associations of the country’s Gross National Income (GNI) per capita, cancer incidence, number of physicians per population, and Gini index with the number of new cancer drug launches and launch delay in a country, respectively.Results A total of 568 cancer drugs were launched for the first time globally between 1990 and 2022. Among these, 35% had been launched in only one country by 2022, 22% in 2–5 countries, 15% in 6–10 countries, and 28% in more than 10 countries. The number of new cancer drugs launched in a country in this period ranged from 0 to 345. The average delays from the first global launch to the second, third, fourth, and fifth launch were 18.0 months, 24.3 months, 32.5 months, and 39.4 months, respectively. Our multivariate models showed that higher GNI per capita and cancer incidence in a country were associated with more launches and shorter delays.Conclusion This research reveals significant disparities in the availability and timeliness of availability of new cancer drugs across countries. These disparities are likely to have contributed to the poor cancer outcomes observed in many countries.